catena-Poly[[di-μ-aqua-bis[aquacobalt(II)]]-bis(μ3-1H-benzimidazole-5,6-dicarboxylato] (Acta Crystallographica Section E, 2009)
The title compound, [Co2(C9H4N2O4)2(H2O)4]n, is a one-dimensional polymeric complex with bridging 1H-benzimidazole-5,6-dicarboxylate and aqua ligands. The CoII cation has an octahedral coordination environment provided by an NO5 donor set. Adjacent polymeric chains extended along the [100] direction are linked by O—H...O and N—H...O hydrogen bonds, generating a three-dimensional network.